Evaluation and care of a polytraumatized patient - Lovrenčić, Petra (Array, 2019)
Polytrauma is a simultaneous severe injury to at least two body regions where at least one injury, or a combination of multiple injuries, endangers life. The spectrum of injuries and posttraumatic disorders is extremely wide. Most commonly they include shock, hypotension due to bleeding or vital organs injury. Injuries are the leading cause of death in developed countries today, and proportion of people who experience polytrauma in the total number of the injured is 3%, with a high mortality rate of 22%. Reanimation procedures and understanding of pathophysiology have progressed remarkably, and in the last twenty years, mortality has decreased by twenty percent. Time is a very valuable factor in the treatment of a polytraumatized patient and requires initiation of injury treatment within 60 minutes of its occurrence. In the clinical approach to treatment, algorithms for the treatment of polytrauma are used to achieve the best results of treatment and to reduce posttraumatic complications. Triage is a formal process through which the condition of all the patients is evaluated right after their arrival at the Emergency Department. Triage determines the urgency of the problem and assesses the allowed and expected waiting time for the beginning of the physician’s examination and treatment of the patient. The approach to a polytraumatized patient is multidisciplinary, includes many specialties and requires continuous education and highly educated staff. High-quality skills, good communication and readiness to respond quickly and efficiently are just some of the key determinants of working with patients with life-threatening conditions.